(untitled) (Research, Society and Development, 2021)
Considering the intensification of anthropic action in natural environments and its harmful effects on human health, the aim of this work was to evaluate the knowledge about the environmental impacts and its relationship with the New Coronavirus in a School in the Municipality of Sumé in Cariri, Paraíba. The selected school in the city was the Agrotécnica Deputado Evaldo Gonçalves de Queiroz. Questionnaires and semi-structured interviews were applied through an electronic form (Google Form). Data were tabulated in an Excel 2019® spreadsheet and analyzed qualitatively and quantitatively. The students demonstrated to be aware of the factors that favor the emergence of zoonotic diseases, the negative impacts generated by the Novo Coronavirus, in addition to the public health measures adopted to reduce the effects of the New Coronavirus and the environmental strategies needed to mitigate them. However, a significant part of them only partially know the problems that cause harmful effects to human health. However, it is necessary to develop methodological teaching-learning strategies that cover factors related to environmental health in the school environment.